Perspectives in Diagnosis and Treatment of Rabies Viral Encephalitis: Insights from Pathogenesis - Mahadevan, Anita (Neurotherapeutics, 2016)
Rabies viral encephalitis, though one of the oldest recognized infectious disease of humans, remains an incurable, fatal encephalomyelitis, despite advances in understanding of its pathobiology. Advances in science have led us on the trail of the virus in the host, but the sanctuaries in which the virus remains hidden for its survival are unknown. Insights into host–pathogen interactions have facilitated evolving immunologic therapeutic strategies, though we are far from a cure. Most of the present-day knowledge has evolved from in vitro studies using fixed (attenuated) laboratory strains that may not be applicable in the clinical setting. Much remains to be unraveled about this elusive virus. This review attempts to re-examine the current advances in understanding of the pathobiology of the rabies virus that modulate the diagnosis, treatment, and prevention of this fatal disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13311-016-0452-4) contains supplementary material, which is available to authorized users.